3D CdS/ZnO/Pt/WO3 nanostructure electrode for enhancing photoelectrochemical water splitting - Hiên, Trương Thị; Vũ, Thị Bích; Phan, Thị Bình; Mai, Thị Thanh Thùy; Mẫn, Minh Tân; Nguyễn, Tiến Đại; Trần, Thị Trang; Chu , Thị Thu Hiền; Trần , Thị Minh Nguyệt; Nguyễn , Mạnh Hùng (Hue University Journal of Science: Natural Science, 2021)
In this work, we report the synthesis of the hierarchical structure of a CdS/ZnO/Pt/WO3 electrode for photoeletrochemical water splitting application. The photoanode was synthesized via the hydrothermal and atomic layer deposition methods. The morphological and structural properties of CdS/ZnO/Pt/WO3 nanoplates were carefully investigated by using SEM, TEM, and XRD techniques. The CdS/ZnO/Pt/WO3-based photoelectrode has a photocurrent density of 8,5 mA·cm-2 and a photoconversion efficiency of 7.9% at a supplied potential of –0,85 V in a 0.5 M Na2S solution. This photocurrent density is twice higher than that of the CdS/ZnO/FTO electrode. Due to built-in potential and efficiently collecting the photo-carriers generated from the ZnO/CdS heterojunction under illumination, the CdS/ZnO/Pt/WO3 electrode exhibits enhanced performance of the photoelectrochemical cell. This is a promising approach to the synthesis of heterojunction layers of semiconductor together with nanostructures for fabricating photoelectrodes of the photoelectrochemical cell to enhance hydrogen production efficiency.